Plan de cogestión de la microcuenca del río Chaguana - Granizo Cardenas, Nazly Fablenca; Aguilar Espinoza, Alexa Dayanara (Machala : Universidad Técnica de Machala, 2025)
The purpose of this project is to establish a co-management plan for the Chaguana River micro-basin, located in the cantons of El Guabo and Pasaje, El Oro province, Ecuador, with the goal of implementing sustainable natural resource management involving all stakeholders. The methodological approach is based on co-management, which is understood as a participatory governance model that promotes local participation: authorities, communities, and other stakeholders. Through participatory processes, the goal is to make joint decisions that are adapted to the context of local needs for the benefit of the micro-basin. Based on the identified problems in the micro-basin, projects will be designed to improve water management and the agricultural system, promote environmental education, and strengthen local human capacities. This co-management plan articulates strategic actions that seek to consolidate a participatory management model, guaranteeing ecological, economic, and social sustainability in the Chaguana River micro-basin.
El propósito de este proyecto es establecer un plan de cogestión para la microcuenca del rio Chaguana, ubicada en los cantones de El Guabo y Pasaje, provincia de El Oro, Ecuador, con el fin de implementar una gestión sostenible de los recursos naturales donde intervengan todos los actores del territorio. El enfoque metodológico se fundamenta en la cogestión, el cual se entiende como un modelo de gobernanza participativo donde promueve la participación local: autoridades, comunidades y demás actores involucrados. A través de los procesos participativos se busca tomar decisiones de manera conjunta que se adapten al contexto de la necesidad local para el beneficio de la microcuenca. A partir de los problemas identificados de la microcuenca se diseñarán proyectos enfocados en mejorar la gestión hídrica, el sistema agrícola, promover la educación ambiental y fortalecer las capacidades humanas locales. Este plan de cogestión articula acciones estratégicas que busca consolidar un modelo de gestión participativo garantizando la sostenibilidad ecológica, económica y social en la microcuenca del Río Chaguana.
Keywords: COGESTIÓN; MICROCUENCA; PARTICIPACIÓN COMUNITARIA; RÍO CHAGUANA